Case Report: Maribavir for refractory cytomegalovirus viremia after renal transplantation in a child with Schimke’s immune-osseous dysplasia - Huang, Jia-Shuan; Wang, Hong-Kai; Rong, Li-Ping; Jiang, Xiao-Yun; Liu, Long-Shan; Huang, Liu-Yi; Zhang, Na; Yue, Zhi-Hui (Frontiers in Immunology, 2025)
Cytomegalovirus (CMV) is a major opportunistic pathogen in recipients of solid organ transplantation. Maribavir, a pUL97 protein kinase inhibitor, was approved for the treatment of refractory post-transplant CMV infection in the US in 2021. However, it is rarely used in pediatric patients worldwide. Here, we report the case of a Chinese boy with Schimke’s immune-osseous dysplasia (SIOD) who developed refractory CMV infection after a renal transplantation. An 11-year-old boy was hospitalized with recurrent abdominal and testicular pain 50 days after renal transplantation. Diagnoses included urinary tract infection, epididymitis, CMV viremia, stage 2 chronic kidney disease, and SIOD. After five days of treatment, his pain improved, but he developed persistent fever and shortness of breath. Blood CMV levels rose to 1.64 × 105 copies/ml after one month of ganciclovir treatment. Significant bone marrow suppression was observed after combined treatment with foscarnet. Anti-rejection treatment was discontinued due to compromised immune function. On day 40, maribavir was initiated with parental consent, resulting in undetectable CMV copies within four days. The patient’s clinical status and bone marrow suppression had improved. Continuing maribavir for two weeks led to the disappearance of CMV viremia, no bone marrow suppression, and normal liver and kidney functions. This case demonstrates the successful short-term use of maribavir in the treatment of refractory CMV infection in an immune-deficient child after renal transplantation. Further studies are required to explore the efficacy and safety of maribavir in pediatric patients.